Sistem E-Cuti Berbasis Website Berbasis Intelligent System untuk Meningkatkan Efisiensi Administrasi Sekolah - Akhsani Taqwiym; Nurussama (Jurnal Software Engineering and Computational Intelligence, 2026)
Leave administration management in elementary schools is still largely conducted manually, resulting in various issues such as unstructured documentation, difficulties in data retrieval, and delays in the approval process. This study aims to design and develop a web-based e-leave application to improve the efficiency and effectiveness of leave management for teaching staff. The system was developed using the Waterfall method, which consists of requirement analysis, system design, implementation, and testing stages. Data collection was carried out through observation, interviews, and documentation to understand the existing system. The results show that the developed e-leave application successfully integrates the entire leave submission process into a structured digital system. The system provides key features such as user authentication, teacher data management, department and position management, leave variables, as well as leave submission and monitoring. System testing was conducted using the Black Box Testing method, and the results indicate that all system functions operate correctly without any errors. The implementation of this system has a positive impact on improving administrative efficiency, accelerating the leave submission and approval process, and enhancing data accuracy and transparency. Therefore, the web-based e-leave application can serve as an effective solution to support digital transformation in educational administration.